Age and diet affect self-resilience of intestinal microbiome in mice - Shao, Chenyi; Chen, Shenmin; Yang, Huan; Li, Mufan; Liu, Yinhui; Wen, Shu; Xiao, Jing; Tang, Li (Frontiers in Microbiology, 2025)
BackgroundGut microbiota contributes to human health. Little is known about the self-resilience of the gut microbiota after dysbiosis. This study aimed to investigate the self-resilience of the gut microbiome at different ages and the effects of diet on its recovery capacity in adulthood.MethodsA rodent model of antibiotic-induced dysbiosis was used. Microscopy was used to observe morphological changes in the mucosa. In addition, 16S rRNA sequencing and polymerase chain reaction-denaturing gradient gel electrophoresis were performed to identify the bacterial taxa and microbiome structure, respectively.ResultsThe diversity of the gut microbiota in infant mice was recovered by the sixth week, while relative abundance of Ruminococcaceae_UCG_014 was low and did not return to normal levels. Gut microbiota in young adult mice recovered in the fourth week. Prevotellaceae and Alloprevotella were significantly higher in the high-fat-diet group than those in the control group. The elderly mice had three, two, four, and seven statistically different genera between the dysbiosis and control groups at weeks 6, 8, 10, and 12, respectively. Intestinal epithelial structure and cecum index are restored with microbiota repaired.DiscussionThe gut microbiota in infant and adult mice is more capable of self- resilience, the composition of the microbiota and mucosal morphology of the intestine can be largely restored. Adding protein and fat to the diet accelerated colony recovery in young adult mice in the short term. In elderly mice, the resilience of the gut microbiota was reduced, and the occurrence of dysbiosis at this stage may accelerate organismal aging and affect the lifespan. A limitation of this study is that all data were derived from mice. Therefore, we must be cautious about translating the microbiome results from mice to humans.